IMPLEMENTASI MANAJEMEN KONFLIK DALAM PENYELESAIAN MASALAH DI MI ASSU’ADA KOTA BANDUNG - Syamsul Fathurrohman; Wahyu Hidayat (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
This study aims to investigate the implementation of conflict management in problem- solving at MI Assu'ada in Bandung City. As an Islamic educational institution, MI Assu'ada has a responsibility to shape the character and personality of students in accordance with Islamic values. However, conflicts that arise within the school environment can disrupt the process of building good character. Therefore, the effective implementation of conflict management becomes crucial in creating a conducive educational environment where students can grow and develop in line with Islamic values. This research utilizes a field research method with a qualitative descriptive approach. Data collected are related to the implementation of conflict management at MI Assu'ada in Bandung City. The findings reveal that MI Assu'ada initially faced various conflicts, particularly between administrators/employees and among students. These conflicts often arise due to differences in perspectives or inappropriate treatment. One specific conflict identified involved a dispute between a teacher and a student's guardian. The guardian expressed concerns about the teacher's treatment towards their child, while the teacher felt that the student did not comply with rules and assigned tasks. However, through the implementation of conflict management, the school successfully resolved the conflict. In conclusion, the implementation of conflict management at MI Assu'ada in Bandung City has helped address conflicts within the school environment. With a good approach, open communication, and appropriate handling, the school has been able to create a conducive educational environment for students. This research provides insights into the importance of implementing conflict management in Islamic education and contributes to the development of effective conflict resolution approaches within educational settings.